ANALYSIS OF THE APPLICATION OF LITERACY CULTURE IN EARLY CHILDREN - Andi Saadillah; Rudi Karma; Nurul Haeniah; Herawati Herawati; Sulistiawati Sulistiawati (Jurnal Scientia, 2022)
In early childhood, literacy is usually done with activities that are fun and attract the attention of students such as playing. The introduction of literacy activities of listening, speaking, reading and writing to children is applied without any coercion on children. At this stage, the introduction of literacy that is appropriate to an early age or its developmental phases is one of the reasons behind this research. Researchers want to know how to apply literacy culture and what are the obstacles faced by teachers to elementary school students at SDN 1 Horongkuli Kab. Kolaka. The type of research used in the form of qualitative research with data obtained based on the activities of students at SDN 1 Horongkuli Kab. Kolaka in applying literacy culture. Data collection techniques in the form of direct observation or observation, interviews, recordings of teachers and students of SDN 1 Horongkuli. Results Based on the research, it was found that the implementation of literacy culture in early childhood, especially at SDN 1 Horongkuli Kab. Kolaka is to cultivate reading activities in class at least 10 minutes before entering learning, reading picture books, guiding children to literacy games, holding speed reading competitions, scheduling visits to the library, and making activities based on daily activities. The obstacles faced are from internal factors, the characteristics of students who are different in receiving learning materials so that there are still some students who are less interested in literacy activities that are applied by the teacher. Furthermore, external factors are the availability of story books that still need to be improved, as well as the lack of participation from parents.